Specific prime movers` excitation during free-weight bench press variations and chest press machine in competitive bodybuilders - Coratella, G.; Tornatore, G.; Longo, S.; Esposito, F.; Cè, E. (European Journal of Sport Science, 2020)
The current study compared the muscle excitation in free-weight bench press variations and chest press machine. Ten competitive bodybuilders were recruited. The EMG-RMS amplitude of clavicular and sternocostal head of pectoralis major, long head of triceps brachii and anterior and lateral deltoid was recorded while performing horizontal (BP), inclined (45°) (IBP) or declined (-15°) bench press (DBP) and chest press machine (CP). Four non-exhaustive repetitions were performed using 80% of 1-repetition maximum of each exercise. Both concentric and eccentric phases were recorded. During the concentric phase, [d effect size: 2.78/7.80] clavicular head was more excited in IBP and less excited in CP (d: -9.69/-4.39) compared to all other exercises. The sternocostal head was similarly excited in DBP vs. BP and BP vs. CP and more excited (d: 2.42/9.92) compared to IBP. Triceps brachii excitation was overall greater (d: 2.01/6.75) in BP and DBP compared to all other exercises. Anterior deltoid was less excited (d: 3.84/19.77) in DBP compared to all other exercises. Lateral deltoid excitation was greater (d: 0.96/3.10) in BP, IBP and DBP compared to CP. Muscle excitation during the eccentric phase followed a similar pattern, with the exception of the greater (d: 3.89/11.32) excitation in the clavicular head in BP compared to all other exercises. The present outcomes showed that the excitation of the clavicular and sternocostal head of pectoralis major depends on the bench inclination angle. The use of BP variations vs. CP allows overall greater triceps brachii and lateral deltoid excitation, due to the greater instability.